Sensory characteristics and the difference law of volatile components in rounds base liquor of sauce-flavor Baijiu - ZHU Xiaochun, WU Lan, SHANG Yuhao, SUN Youlan, YOU Xiaolong, HU Jianfeng, HU Feng (Zhongguo niangzao)
In this study, using the 1st to the 7th rounds of base liquor of sauce-flavor (Jiangxiangxing) Baijiu as research objects, the sensory characteristics and volatile components were analyzed by quantitative descriptive analysis (QDA), gas chromatography-mass spectrometry (GC-MS), and gas chromatography (GC), and the differences of volatile components and their correlation with sensory attributes were analyzed by orthogonal partial least squares discriminant analysis (OPLS-DA) and partial least squares regression (PLSR) analysis, respectively. The results showed that the 1st and 2nd rounds of base liquor had obvious grain, sour and fruity aroma with prominent sourness, the 3rd, 4th and 5th rounds of base liquor had floral, grassy, sauce, Daqu and pasty aroma with obvious aftertaste of sweetness and purity, while the 6th and 7th rounds of base liquor presented strong pasty and Daqu aroma, highlighted by bitterness and aftertaste. A total of 272 volatile components were identified from the base liquor of each round. In terms of categories, esters were the most abundant, and the differences in the types of substances between rounds were mainly concentrated on esters, aldehydes and ketones. In terms of content, as the number of rounds increased, the contents of alcohols, esters and acids showed a decreasing trend, while the others showed an increasing trend. Based on the variable importance in the projection (VIP)>1 and the odor activity value (OAV)>1, 13 main components contributed to content difference and 45 important components contributed to aroma difference were screened from the base liquor of each round, respectively, which were correlated with the sensory attributes of base liquor of each round.